Analisis Peran, Tujuan, dan Komponen Layanan Bimbingan Konseling pada Pendidikan Sekolah Dasar - Zahroh, Fatimatus; Avivah, Evi Nur; Anggara, Fera Septi; Aulia, Fitria Nurul; Wahyuda, Bima; Rusmiyati, Rusmiyati (Indo-MathEdu Intellectuals Journal, 2025)
This study discusses the role, objectives, and components of Guidance and Counseling (BK) services in elementary schools. BK functions to help students develop their potential, character, and social and academic abilities. The service objectives include addressing personal, social, academic, and career planning issues in a targeted manner. This study uses a qualitative literature review approach. Data sources were obtained from scientific journals, books, and official documents accessed through Google Scholar, Garuda, and DOAJ. Data were collected using a systematic literature search and snowballing techniques, then analyzed using content analysis to identify key themes related to the implementation of Guidance and Counseling services. Based on the literature analysis, Guidance and Counseling services in elementary schools are implemented through four main components: basic services, responsive services, individual planning, and system support. These four components support each other to create holistic student development. These findings emphasize the importance of collaboration between teachers, principals, and parents to build a conducive learning environment and support the successful implementation of BK.